2021
DOI: 10.3389/fneur.2021.717239
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Non-motor Symptoms and Quality of Life After Deep Brain Stimulation for Refractory Dystonia: A 1-Year Follow-Up

Abstract: Introduction: Deep brain stimulation (DBS) is a treatment option for refractory dystonia's motor symptoms, while its non-motor symptoms (NMS) have been less systematically assessed. We aimed to describe the effects of DBS on NMS in refractory generalized inherited/idiopathic dystonia prospectively.Methods: We evaluated patients before and 1 year after DBS surgery and applied the following scales: Burke–Fahn–Marsden Rating Scale (BFMRS), NMS Scale for Parkinson's Disease (NMSS-PD), Parkinson's Disease Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Here too, pain intensity did not correlate with severity of motor symptoms. This further supports the view that motor symptoms and NMS such as pain are likely to not only depend on different mechanisms but also respond differently to treatment and have different prognoses 42,56 …”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Here too, pain intensity did not correlate with severity of motor symptoms. This further supports the view that motor symptoms and NMS such as pain are likely to not only depend on different mechanisms but also respond differently to treatment and have different prognoses 42,56 …”
Section: Discussionsupporting
confidence: 73%
“…12 Additionally, efficacious treatments to control dystonic movements may not wholly mitigate pain in PwD, which persists despite improvement in motor symptoms. 35,42 The main driving mechanism of dystonia is believed to be the reduction in cortical inhibition, impaired synaptic plasticity, and altered gain in somatosensory processing. [43][44][45][46][47][48][49] Our data show that CP's severity and impact did not correlate with dystonia's motor severity or disability.…”
Section: T H E D Y S T O N I a -P A I N C L A S S I F I C A T I O N S...mentioning
confidence: 99%
See 2 more Smart Citations
“…For DBS reporting of NMS, especially in adult-onset focal dystonia, is scarce. A review based on studies with limited cohort sizes showed positive effects on pain [21], and a prospective study in generalized dystonia demonstrated improvement in a wide array of NMS [22 ▪ ]. Nonetheless, there is a promising development with several recent publications stressing the importance of NMS in the treatment of patients with dystonia, advocating for a more holistic approach [23–25].…”
Section: Nonmotor Symptomsmentioning
confidence: 99%